Pengaruh Kualitas Pelayanan, Fasilitas, Harga dan Citra Institusi Terhadap Kepuasan Pasien: Studi di Klinik Rawat Jalan Nuurul Ichsan Pujon dan Klinik Intan Mandiri Malang - Widya Agustin Setyawati; Muhamad Rifa'i; Cahyo Sasmito (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
Along with the increasing awareness of the importance of health for the community, as well as the rapid development of health technology, this is a claim against a quality health services in order to meet the basic needs of the the community. This research conducted in October to January 2017 2018 by using multiple linear regression analysis. Total population of 1034 patients with the sample slovin formula in the get 100 patients. Data retrieval is done by spreading the questionnaire to obtain primary data related to the influence of the quality of service, amenities, price and image of the institution against the patient's satisfaction. Research results on the Test F obtained the value of F-hitung > F-critical so the zero hypothesis is rejected, the conclusion that is the quality of service, amenities, Price and image of influential Institutions simultaneously against the patient's Satisfaction. And from the four variables such variable is the most dominant image of the institution) because it has a value of the t-table of highest.